EXAMINING PHILOSOPHICAL VIEWS UNDERLYING THE DESIGN OF ENGLISH TEACHER’S LESSON PLAN AND THE TEACHING MATERIALS - Ilmi Safrizal (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2022)
This study is correlational research that attempts to examine philosophical views underlying the design of an English teacher’s lesson plan and the teaching materials. Inferential content analysis is employed in this study to find the correlations between the teacher’s documents and the philosophical views which influence the teacher during the process of development. A face-to-face interview with the teacher is also conducted in this study to explore why the teacher uses a certain approach for teaching English and how aware the teacher is of the philosophical views underlying the approach. This study found that there are six philosophical views, including essentialism, perennialism, progressivism, socio-reconstructionism, humanism, and idealism, which influence the design of the lesson plans and the teaching materials. However, although those six philosophical views are implied on the teacher’s documents, essentialism is the most influencing philosophy which has a big impact on the teacher in deciding what activities are suitable for the students. Drilling activities, such as vocabulary enhancement, pronunciation practices, are happened in almost every meeting.